2015
DOI: 10.3389/fmicb.2015.01371
|View full text |Cite
|
Sign up to set email alerts
|

The Capability of Tyramine Production and Correlation between Phenotypic and Genetic Characteristics of Enterococcus faecium and Enterococcus faecalis Strains

Abstract: The aim of this study was to investigate the diversity of tyramine production capability of four Enterococcus strains in buffered systems in relation to their genetic characteristics and environmental conditions. Cells of the strains Enterococcus faecalis EF37 and ATCC 29212, and E. faecium FC12 and FC643 were re-suspended in phosphate/citrate buffers with different pH, NaCl concentration and incubation temperature. At intervals, cell viability and tyramine production were assessed by plate counting and HPLC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 49 publications
(72 reference statements)
4
34
0
Order By: Relevance
“…This trend was also observed by Bargossi et al . () in the strains E. faecalis EF37 and E. faecium FC12; however, in the same experiment, the strains E. faecalis ATCC 29212 and E. faecium FC643 produced tyramine only after reaching the stationary phase. These differences were partially explained by different transcription levels of the gene tyrDC .…”
Section: Introductionmentioning
confidence: 75%
See 4 more Smart Citations
“…This trend was also observed by Bargossi et al . () in the strains E. faecalis EF37 and E. faecium FC12; however, in the same experiment, the strains E. faecalis ATCC 29212 and E. faecium FC643 produced tyramine only after reaching the stationary phase. These differences were partially explained by different transcription levels of the gene tyrDC .…”
Section: Introductionmentioning
confidence: 75%
“…This heterogeneity has been recently evidenced in two strains of E. faecalis (EF37 and ATCC 29212) and two of E. faecium grown in nutritionally rich or poor media, added or not with tyrosine (Bargossi et al . ). This paper focused on deeper studies about the heterogeneity concerning tyrDC activity observed in the two E. faecalis strains.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations